Medicinal Uses and Phytochemical Properties of Ageratum conyzoides: An Advanced and Empirical Review - Moses Sunday Afariogun (Darul Yasin Al Sys, 2025)
Goat Weed (Ageratum conyzoides L.) is a tropical medicinal herb traditionally employed for wound healing, fever reduction, and inflammation management. This review consolidates evidence confirming its antimicrobial, anti-inflammatory, and wound-healing properties, primarily attributed to bioactive constituents such as precocenes, flavonoids, and terpenoids. Despite its pharmacological promise, the presence of pyrrolizidine alkaloids presents hepatotoxicity risks, underscoring the need for standardized formulations. Studies highlight its efficacy against various pathogens, its capacity to modulate inflammatory pathways (TNF-α/NF-κB), and its ability to stimulate collagen production during wound repair. Beyond therapeutic applications, A. conyzoides exhibits potential as a natural herbicide and biopesticide. Future research priorities include well-structured clinical trials, nanoformulation development to improve bioavailability, and biotechnological approaches for optimized production.